EFEKTIVITAS DAN DAMPAK REVITALISASI PASAR TRADISIONAL TERHADAP PENDAPATAN PEDAGANG DAN JUMLAH KUNJUNGAN - Nia Permatasari, Ni Kadek; Djinar Setiawina, Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024, 2024)
One of the links in the company's business chain is the world center. The government aims to overcome the weaknesses of traditional markets by reviving traditional markets. The purpose of this study is to analyze the effectiveness and traces of the revival of traditional markets on business income and the number of visits to Pasar Anyar Sari Denpasar City. For this study, 152 respondents were selected from a total population of 590 using random sampling method. Descriptive analysis and two-dimensional differential test with paired samples were used as data analysis methods. Based on the results of the analysis and discussion, it can be interpreted that based on the income, process and output variables, it shows that the traditional market stimulation program at Anyar Sari Market is quite effective, namely 72.08 percent and traditional. The marketing stimulus program for Anyar Sari Market has had a positive impact on revenue and traffic of traders at Anyar Sari Market, Denpasar City. The effectiveness of the implementation of the traditional market revitalization program at Pasar Anyar Sari is quite effective. It is hoped that market leaders will continue to improve service and speed of response to various complaints from sellers.